2005
DOI: 10.1093/jac/dki026
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone-resistant Pseudomonas aeruginosa: risk factors for acquisition and impact on outcomes

Abstract: FQ exposure from widespread prescribing is a modifiable risk factor for FQ resistance in P. aeruginosa. FQ empirical therapy for Pseudomonas infections may be associated with significant delays in administering effective therapy resulting in adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 25 publications
8
51
1
4
Order By: Relevance
“…Previous studies have shown that prior treatment with fluoroquinolone is a risk factor for colonization with MDR P. aeruginosa, and this resistance is associated with a poor clinical outcome for infected patients (Gasink et al, 2006;Hsu et al, 2005). Consistent with the findings from other investigations, our study identified by univariate analysis that mortality associated with fluoroquinolone resistance is significant (P50.023) (data not demonstrated).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that prior treatment with fluoroquinolone is a risk factor for colonization with MDR P. aeruginosa, and this resistance is associated with a poor clinical outcome for infected patients (Gasink et al, 2006;Hsu et al, 2005). Consistent with the findings from other investigations, our study identified by univariate analysis that mortality associated with fluoroquinolone resistance is significant (P50.023) (data not demonstrated).…”
Section: Discussionsupporting
confidence: 92%
“…aeruginosa has a wide spectrum of intrinsic and acquired antimicrobial resistance mechanisms (Breidenstein et al, 2011;Morales et al, 2012). Carbapenem resistance frequently results from the production of b-lactamases, particularly b-lactamases that hydrolyse carbapenems, such as MBL (Breidenstein et al, 2011;Sader et al, 2005;Van der Bij et al, 2011 Previous studies have shown that prior treatment with fluoroquinolone is a risk factor for colonization with MDR P. aeruginosa, and this resistance is associated with a poor clinical outcome for infected patients (Gasink et al, 2006;Hsu et al, 2005). Consistent with the findings from other investigations, our study identified by univariate analysis that mortality associated with fluoroquinolone resistance is significant (P50.023) (data not demonstrated).…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, despite the limitations, the analysis in this current study offers a preliminary picture on potential association to call for a large scale-study, particularly the association of antibiotic exposure and duration of hospital stay which have been shown to be significant in this study. Other similar associations have also been reported by many studies regardless of the socio-economic factors of the studied sample (Aloush et al 2006;Hsu et al 2005;Lodise et al 2007;Shanthi & Sekar 2009). These can be undoubtedly understood as antibiotic exposure will cause selective pressure for MDRPA to proliferate while hospital stay will increase the likelihood of acquiring the nosocomial spread.…”
Section: Discussionsupporting
confidence: 87%
“…The risk factors that are included in this study have also been investigated by many other researchers but whether those were significantly associated with the isolation of MDRPA had been differentially reported (Aloush et al 2006;Bahmani & Ramazanzadeh 2013;Gibu et al 2010;Hsu et al 2005;Lodise et al 2007;Shanthi & Sekar 2009). These are due to the variability in the socio-economic and health status of the studied population, as well as sample size in the respective study's setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation